Molecular identification and characterization of a bacterium that has potential to degrade low concentration of haloalkanoic acid - Amini, S; Zulkifly, Ahmad Hafiz; Wong, Wen-Yong; Huyop, Fahrul (Academic Journals Inc., 2011)
Most halogenated compounds are major environmental pollutants. Pollution from industrial chemicals and herbicide/pesticide from agricultural activities cause problem to the society. The main objectives were to isolate and characterize the bacterium that can grow in halogenated substrate as the sole source of carbon. A common microbiological and molecular techniques were adapted for further characterization. In current study, a soil microorganism, identified as Aminobacter sp. SA1 by partial biochemical and 16S rRNA sequencing method was isolated with 2,2DCP (2,2-dichloropropionic acid) as the sole carbon and energy source. This bacterium has the ability to degrade 2,2DCP (2,2-dichloropropionic acid) and D,L2CP (D,L-2-chloropropionic acid) at 20 mM with cells doubling time of 7 h in 2,2DCP medium. The bacterium was able to grow at low substrate concentration of 1 mM 2,2DCP (20 times lower than normal growth concentration) with cells doubling time of approximately 7 h suggesting the dehalogenase enzyme(s) that present in the bacterium has high affinity towards the substrate. However, at 0.1 mM 2,2DCP (200 times lower than normal concentration) no halide ions were detected in the growth medium suggesting no growth was observed. The investigation highlighted degradation at low substrate concentration suggested that the isolated bacterium can live in low level of halogenated compounds. This observation may or may not involve new kinds of dehalogenases. The presence of more than one dehalogenases in a bacterial system is far from clear